Impacto de las enfermedades profesionales en el desempeño laboral de los colaboradores de las empresas ubicadas en el barrio Cochapamba D.M.Q. - Parra Calva, María Amelia (2015)
The reader in this research paper will find information about occupational diseases and accidents, as these two factors influence job performance of an employee regardless of the activity performed in various jobs. They should be investigated workers and managers of industrial enterprises in the neighborhood Cochapamba, their knowledge both parties about the laws and regulations on Industrial Safety and Occupational Health, dissemination that exists in each of be analyzed companies on this subject, what are the preventive and corrective measures taken by management for workers enjoy better health in the workplace. With the analyzes performed by different techniques such as observation, survey and interview, it gets conclusions and verifications about compliance with both internal policies and external laws that protect worker health, important in any organization element, which are partakers in achieving organizational objectives, departmental thereby generating greater utility and performance in enterprises.